Effects of short-term hyperoxemia on cerebral autoregulation and tissue oxygenation in acute brain injured patients - Ciliberti, Pietro; Cardim, Danilo; Giardina, Alberto; Groznik, Matjaž; Ball, Lorenzo; Giovannini, Martina; Battaglini, Denise; Beqiri, Erta; Matta, Basil; Smielewski, Peter; Czosnyka, Marek; Pelosi, Paolo; et al. (Frontiers in Physiology, 2023)
Introduction Potential detrimental effects of hyperoxemia on outcomes have been reported in critically ill patients. Little evidence exists on the effects of hyperoxygenation and hyperoxemia on cerebral physiology. The primary aim of this study is to assess the effect of hyperoxygenation and hyperoxemia on cerebral autoregulation in acute brain injured patients. We further evaluated potential links between hyperoxemia, cerebral oxygenation and intracranial pressure (ICP). Methods This is a single center, observational, prospective study. Acute brain injured patients [traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), intracranial hemorrhage (ICH)] undergoing multimodal brain monitoring through a software platform (ICM+) were included. Multimodal monitoring consisted of invasive ICP, arterial blood pressure (ABP) and near infrared spectrometry (NIRS). Derived parameters of ICP and ABP monitoring included the pressure reactivity index (PRx) to assess cerebral autoregulation. ICP, PRx, and NIRS-derived parameters (cerebral regional saturation of oxygen, changes in concentration of regional oxy- and deoxy-hemoglobin), were evaluated at baseline and after 10 minutes of hyperoxygenation with a fraction of inspired oxygen (FiO2) of 100% using repeated measures t-test or paired Wilcoxon signed-rank test. Continuous variables are reported as median (interquartile range). Results Twenty-five patients were included. The median age was 64.7 years (45.9-73.2), and 60% were male. Thirteen patients (52%) were admitted for TBI, 7 (28%) for SAH, and 5 (20%) patients for ICH. The median value of systemic oxygenation (partial pressure of oxygen - PaO2) significantly increased after FiO2 test, from 97 (90-101) mm Hg to 197 (189-202) mm Hg, p0.0001. After FiO2 test, no changes were observed in PRx values (from 0.21 (0.10-0.43) to 0.22 (0.15-0.36), p0.68), nor in ICP values (from 13.42 (9.12-17.34) mm Hg to 13.34 (8.85-17.56) mm Hg, p0.90). All NIRS-derived parameters reacted to hyperoxygenation as expected. Changes in systemic oxygenation and the arterial component of cerebral oxygenation were significantly correlated (respectively ΔPaO2 and ΔO2Hbi; r  0.49 (95% CI = 0.17-0.80).